Critical factors for a successful logo : the EDP Serviço Universal case - Marques, Bernardo Maria Magalhães Mexia Gomes (2018)
The new regulation of the Portuguese regulated electricity market imposes several challenges to brands that want to integrate this sector, but at the same time, it offers an opportunity for companies to differentiate themselves from the competition and thus gain a competitive advantage. In order to achieve this much-desired competitive advantage and to establish the best strategy for the new brand, EDP SU had the need to understand what the preferences of consumers are regarding brands in this sector. Thus, this dissertation focuses on exploring the main factors that influence consumers' perceptions and what variables determine the choices they make. The study focuses specifically on the attributes and associations of the brand, name and logo. The present study presents a comprehensive literary review, which addresses topics that are essential for maximizing a brand and for a full understanding of consumers’ behaviour, such as: Branding, Brand Equity, Brand Personality, Brand Elements, Name, Logo and Colour. Moreover, this dissertation has a market study that includes eleven focus groups and a Benchmark analysis. The results show that EDP should seek a name that explains the energy it sells, that must use two or more colours and that must create a brand that conveys a mature and traditional image.